2005
DOI: 10.1381/0960892053576596
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic Steatohepatitis (NASH) and Hepatocellular Carcinoma

Abstract: Non-alcoholic fatty liver disease (NAFLD) is characterized by an excessive accumulation of fatty acids and triglycerides within the cytoplasm of the hepatocytes of non-alcohol users. The natural history varies according to the initial histological diagnosis. A current consideration is that cryptogenic cirrhosis may be representative of a late stage of non-alcoholic steatohepatitis (NASH), which has lost its features of necroinflammatory activity and steatosis in up to 80% of patients. Since NASH is able to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 22 publications
1
59
0
1
Order By: Relevance
“…8,52,57,[93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109] Male patients make up the majority of cases with a mean age at diagnosis of 66.7 (range ¼ 45-82). The patients are typically older at presentation than patients with HCC related to other chronic liver diseases.…”
Section: Case Reports and Case Series Of Nash And Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…8,52,57,[93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109] Male patients make up the majority of cases with a mean age at diagnosis of 66.7 (range ¼ 45-82). The patients are typically older at presentation than patients with HCC related to other chronic liver diseases.…”
Section: Case Reports and Case Series Of Nash And Hccmentioning
confidence: 99%
“…Up to 50% of patients have HCC at the time of initial referral, and rarely patients present with HCC in the absence of cirrhosis. 8,93,94,96,101,[105][106][107][108][109] The fact that HCC can arise in the setting of NASH without underlying cirrhosis raises the interesting possibility that carcinogenesis can occur in NAFLD in the absence of advanced liver disease. 108 Three recent case studies of patients with HCC in the setting of NASH support the findings of previous case reports.…”
Section: Case Reports and Case Series Of Nash And Hccmentioning
confidence: 99%
“…It has been observed that at the time of diagnosis, advanced fibrosis is already found in 30-40% of NASH patients, and 10-15% already have established cirrhosis. Since NASH may progress to cirrhosis (NASH being responsible for 70% of cryptogenic cirrhosis) [128], HCC development may be a part of the natural history of this disease [129]. A recent study by Chen et al [58], which enrolled 23,820 residents in Taiwan with a 14-year followup, showed that extreme obesity (BMI C 30 kg/m 2 ) was independently associated with a fourfold risk of HCC in anti-HCV-positive subjects and a twofold risk of HCC in those without HBV or HCV after controlling for other metabolic components.…”
Section: Nash and Hccmentioning
confidence: 99%
“…There is some evidence that HCC may develop as the last step in the natural history of progressive NASH, based on case reports of HCC in patients with NASH-related cirrhosis from various parts of the world, including Southern Europe (Cotrim et al, 2000;Zen et al, 2001;Shimada et al, 2002;Cuadrado et al, 2005). Almost all the HCC cases had obesity and/or type II diabetes, and they were all negative for HBsAg and anti-HCV, with biopsy-based diagnosis of NASH-related cirrhosis.…”
Section: Non-alcoholic Steatohepatitis and Hepatocellular Carcinomamentioning
confidence: 99%